Nanocoating-konjac application as postharvest handling to extend the shelf life of Siamese oranges - Suriati, Luh (Frontiers in Sustainable Food Systems, 2023)
Siamese orange fruit is very popular today, driven by the increasing public demand or healthy food. Siamese oranges contain bioactive phenolic compounds, carotenoids, vitamins, minerals, and fiber which are good for health. The weakness of Siamese oranges is their quality declines quickly and their short shelf life. Postharvest handling with the application of coatings from natural ingredients to extend the shelf life of orange fruits is currently needed to reduce the use of synthetic materials. Natural ingredients that have the potential to be used as base materials for coatings are konjac tubers because they contain glucomannan polysaccharides and bioactive compounds that can form coatings. The purpose of this study was to determine the effect of nanocoating-konjacon the shelf life of Siamese oranges. The research began with the preparation of the nanocoating-konjac formula as the main ingredient of the nanocoating and the application of the nano coating-konjac on the surface of Siamese oranges. This study used a completely randomized two-factor design, namely nanocoating-konjac application (without coating, coating, and nanocoating) and storage time (0, 5, 10, and 15 days), three replications. Variables observed: Weight loss, number of damaged fruits, color, texture, acidity, total soluble solids, water content, vitamin C, and total plate count. The data obtained was tested for diversity with SPSS, if it shows differences the test is continued with Duncan's Multiple Range Test. The conclusion of this research is the application of nanocoating-konjac, coating-konjac and without coating on Siamese oranges to determine the effect of weight loss, number of damaged fruits, color, texture, acidity, total dissolved solids, water content, vitamin C, and total plate count during storage. This research recommends that the application of nanocoating-konjac as postharvest handling can extend the shelf life of Siamese oranges until the 10th days.